2004
DOI: 10.1029/2004gl021000
|View full text |Cite
|
Sign up to set email alerts
|

Detection of potential fishing ground for albacore tuna using synoptic measurements of ocean color and thermal remote sensing in the northwestern North Pacific

Abstract: To describe potential fishing ground of albacore in relation to dynamics of bio‐physical of their environments, and to clarify impact of El Niño 1998 and La Niña 1999 on tuna fishery, satellite images of SST (TRMM/TMI and NOAA/AVHRR) and SSC (SeaWiFS) together with catch data were used. The 20°C SST and the 0.3 mg m−3 SSC were considered as good indicators of the productive fishing ground. Results showed that a small distance between latitudinal mean position of the SST and the SSC during winter term tended to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(40 citation statements)
references
References 9 publications
1
38
0
1
Order By: Relevance
“…Albacore tuna stock was shown to follow this chlorophyll front movement which was substantially correlated with El Niño and La Niña events. The relationship of albacore tuna to El Niño and La Niña events has also been shown in [18] and [19] where albacore shows low recruitment during El Niño and high during La Niña events. Albacore tuna recruitment in the Pacific has been shown to be correlated to the climatic indices of El Niño Southern Oscillation (ENSO) and Pacific Decadal Oscillation [18].…”
Section: Introductionmentioning
confidence: 70%
See 1 more Smart Citation
“…Albacore tuna stock was shown to follow this chlorophyll front movement which was substantially correlated with El Niño and La Niña events. The relationship of albacore tuna to El Niño and La Niña events has also been shown in [18] and [19] where albacore shows low recruitment during El Niño and high during La Niña events. Albacore tuna recruitment in the Pacific has been shown to be correlated to the climatic indices of El Niño Southern Oscillation (ENSO) and Pacific Decadal Oscillation [18].…”
Section: Introductionmentioning
confidence: 70%
“…Lehodey [18] showed that the time series pattern for the South Pacific albacore tuna from the early 1960s to 2000 was related to the PDO time series trajectory. The relationship of El Niño and La Niña events and the related ENSO and SOI have been shown to be correlated to tuna stocks in the Pacific Oceans previously [12] [18] [19]. Indeed, exploratory analysis did show significant relationship between PDO, SOI and Niña 3 with El Niño events dominating during high Niña 3 SST and La Niña events dominating during low Niña 3 SST (Figure 13).…”
Section: Discussionmentioning
confidence: 97%
“…They also found that regions of tuna abundance occurred in relatively high eddy kinetic energy and geostrophic currents, showing that tuna aggregations were associated with anticyclonic eddies. These eddies may concentrate and trap albacore prey, producing productive fishing grounds (Zainuddin, Saitoh, Saitoh 2004). Sund et al (1981) summarized the relationships between tuna distribution and abundance (larvae, juveniles and adults) and environmental properties of the Pacific Ocean, and tuna behavior in relation with their habitat (Santos 2000).…”
Section: Environmental Indicators Of Fish Distributionmentioning
confidence: 99%
“…Phillips et al (2014) determined the presence of significant relationship between the PDO and SST variability and the spatial distribution of the juvenile North Pacific albacore tuna catch per unit effort (CPUE) off the United States West coast. In the South Pacific, albacore recruitment has been shown to be correlated to the El Niño Southern Oscillation (ENSO) climatic index and the related El Niño and La Niña events (Lehodey et al, 2003;Zainuddin et al, 2004). The North Pacific albacore productivity has been shown to have significant link with the dynamics of ENSO (Zhang et al, 2014).…”
Section: Introductionmentioning
confidence: 99%